EKSPLORASI MAKNA DARI PUISI “DOA" KARYA CHAIRIL ANWAR MELALUI ANALISIS SEMIOTIKA - Susanti, Gina Komara; Novidayanti, Nur Rizky; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to explore the meaning of the poem “Doa” (Prayer) by Chairil Anwar through Roland Barthes’ semiotic approach. The analysis focuses on three layers of meaning: denotation, connotation, and myth. The findings reveal that “Doa” contains deep spiritual and existential dimensions that cannot be interpreted superficially but require a close and layered reading to uncover its hidden meanings. Using Barthes’ semiotic theory—which emphasizes the three levels of meaning—an examination of the poem’s lines unveils the symbolic complexity crafted by the poet. Lines such as “At Your door I knock” and “I cannot turn away” denote simple actions, yet connotatively reflect the fragile human psyche filled with regret, longing, and hope for the divine. At the mythic level, the poem constructs an ideological narrative about the relationship between human beings and God within the context of modernity, where individuals face existential emptiness and ultimately seek refuge in the divine as their only source of meaning and stability.